2019
DOI: 10.7759/cureus.4010
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Gensini Score and Duration of Diabetes in Patients Undergoing Coronary Angiography

Abstract: Introduction The relationship between the duration of diabetes mellitus and coronary artery disease (CAD) is well established. Moreover, the Gensini score system is a reliable assessment tool for the severity of coronary artery disease (CAD). After an extensive literature search, we found that there is a knowledge gap about the relationship between the Gensini score and the duration of diabetes in our population. Therefore, the aim of this study was to find the relationship between the Gensini score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In contrast to other available ISR risk strati cation tools, the Gensini score is a reliable and easily calculated scoring tool and therefore may be applied in daily practice to predict ISR with DES. The Gensini score was originally intended to quantify the severity of CAD, Razi et al [26] found a signi cant positive correlation between Gensini score and the duration of diabetes. However, subsequent studies have shown that it is able to identify patients at high risk of adverse events treated with PCI [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other available ISR risk strati cation tools, the Gensini score is a reliable and easily calculated scoring tool and therefore may be applied in daily practice to predict ISR with DES. The Gensini score was originally intended to quantify the severity of CAD, Razi et al [26] found a signi cant positive correlation between Gensini score and the duration of diabetes. However, subsequent studies have shown that it is able to identify patients at high risk of adverse events treated with PCI [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The Gensini score was used to evaluate the severity of atherosclerosis as described previously. 21 , 22 …”
Section: Methodsmentioning
confidence: 99%
“…The Gensini score was used to evaluate the severity of atherosclerosis as described previously. 21,22 Statistical analysis SPSS Statistics for Windows, Version 17.0 (SPSS Inc., Chicago, IL, USA) was used for statistical analysis. Measurement data were presented as the mean AE standard deviation or median (inter-quartile range).…”
Section: Coronary Angiography and Coronary Gensini Scorementioning
confidence: 99%
“…The Gensini score attempts to quantify the functional significance of a patient's coronary atherosclerotic burden by incorporating a point system for the degree of vessel luminal narrowing that accounts for the specific anatomic location of the stenosis [15]. It is strongly correlated with coronary plaque burden, plaque area, and prognosis [16], and correlates with the duration of other traditional cardiovascular risk factors including smoking [17] and diabetes [18]. However, to our knowledge, only one prior study examined Gensini scores among PLWH presenting with ACS [19].…”
Section: Introductionmentioning
confidence: 99%